Effects of short-term exposure to particulate matters on heart rate variability: A systematic review and meta-analysis based on controlled animal studies. (January 2020) - Huang, Fangfang; Wang, Ping; Pan, Xinjuan; Wang, Yingfang; Ren, Shuai
Abstract: Background: Exposure to particulate matters (PM) is recognized as an important risk factor for cardiovascular disease. A change in cardiac autonomic function is one postulated mechanism leading to PM related cardiovascular events. This study therefore evaluated the associations of short-term exposure to PM and heart rate variability (HRV) parameters, which can reflect the cardiac autonomic function. Methods: Four electronic databases were searched for controlled studies of rodents published prior to December 2018. A systematic review and meta-analysis was conducted. Effect sizes were calculated for five main HRV parameters, including standard deviation of normal-to-normal intervals (SDNN), square root of mean squared differences between successive normal-to-normal intervals (rMSSD), low frequency (LF), high frequency (HF), and the ratio of LF and HF (LF/HF). Results: The review included 23 studies with 401 animals. Short-term exposure to PM by instillation yielded statistically significant effects on SDNN (Standardized Mean Difference [SMD] = −1.11, 95% Confidence Intervals [CI] = −2.22 to −0.01, P  = 0.05), LF (SMD = −1.19, 95% CI = −1.99 to −0.40, P  = 0.003) and LF/HF (SMD = −1.05, 95% CI = −2.03 to −0.07, P  = 0.04). Short-term exposure to PM by inhalation only yielded statistically significant effect on LF/HF (SMD = −0.83, 95% CI = −1.39 to −0.27, P  = 0.004). There was no evidence that animal model and exposure frequency influenced the relationship of PM and HRV. Conclusions: Short-term exposure to PM can decrease HRV of rodents, affecting cardiac autonomic function. Exposure methods can influence the relationships of PM and HRV parameters. Further studies should focus on the effects of long-term PM exposure, on human beings, and potential influential factors of PM-HRV associations. Graphical abstract: Image 1044 Highlights: Short-term exposure to particulate matters can decrease heart rate variability of rodents, affecting cardiac autonomic function. Exposure methods can influence the relationships of particulate matters and heart rate variability parameters. Further studies should focus on the potential influential factors of association between particulate matters and heart rate variability. Abstract : Short-term exposure to PM can decrease HRV of rodents, affecting cardiac autonomic function. Exposure methods can influence the association of PM and HRV.